2018
DOI: 10.1002/mus.26191
|View full text |Cite
|
Sign up to set email alerts
|

Deflazacort versus prednisone/prednisolone for maintaining motor function and delaying loss of ambulation: A post HOC analysis from the ACT DMD trial

Abstract: This analysis, limited by its post hoc nature, suggests greater preservation of 6MWD and 4-stair climb with deflazacort vs. prednisone/prednisolone. A head-to-head comparison will better define these differences. Muscle Nerve 58: 639-645, 2018.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
36
0
3

Year Published

2018
2018
2022
2022

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 49 publications
(39 citation statements)
references
References 24 publications
0
36
0
3
Order By: Relevance
“…Deflazacort is a synthetic heterocyclic corticosteroid obtained by the fusion of methyloxazoline in the prednisone structure with great effectiveness and good tolerability. It causes less retention of sodium, has a strong anti-inflammatory action with immunosuppressive activity, low interference in carbohydrate metabolism and in the metabolism of calcium and phosphorus 49 .…”
Section: Deflazacort Versus Prednisonementioning
confidence: 99%
“…Deflazacort is a synthetic heterocyclic corticosteroid obtained by the fusion of methyloxazoline in the prednisone structure with great effectiveness and good tolerability. It causes less retention of sodium, has a strong anti-inflammatory action with immunosuppressive activity, low interference in carbohydrate metabolism and in the metabolism of calcium and phosphorus 49 .…”
Section: Deflazacort Versus Prednisonementioning
confidence: 99%
“…Steroids, a family of naturally-occurring secondary metabolites characterized by a four-fused ring structure, have exhibited a wide range of biological activities and have been shown to function as antitumoral, antiviral, antibacterial, and antioxidant agents [4]. The heterocyclic corticosteroid deflazacort (DFZ, Figure 1), an oxazoline-derivative of prednisolone, has been recently approved for the treatment of Duchenne dystrophy [5] showing high efficacy and good tolerability. In the frame of a study devoted to the development of a novel and convenient synthetic strategy for the preparation of DFZ, we recently found that a DFZ synthetic precursor called PYED-1 (pregnadiene-11-hydroxy-16α,17α-epoxy-3,20-dione-1), exhibited a good antibacterial activity against Staphylococcus aureus ATCC 29213 and Acinetobacter baumannii ATCC 17978 without showing cytotoxicity [6].…”
Section: Introductionmentioning
confidence: 99%
“…23 The posthoc analysis using the placebo arm from the trial studying another medication, Ataluren (discussed later), showed less mean decline from baseline to 48 weeks in the 6-minute walk test (6MWT), lower mean declines from baseline in the four-stair climb, and longer duration of ambulation in deflazacort-treated patients compared with prednisone/prednisolone-treated patients. 24 No significant differences were noticeable in the safety profiles; however, the deflazacort-treated group had a smaller mean increase in weight and BMI and a smaller mean increase in height.…”
Section: Duchenne Muscular Dystrophymentioning
confidence: 83%